Colonization of the entomopathogenic fungus Beauveria bassiana (Bals.) Vuill. on rice and its impact on nymph mortality and fecundity of brown planthopper (Nilaparvata lugens Stål): Kolonisasi cendawan entomopatogen Beauveria bassiana (Bals.) pada tanaman padi dan pengaruhnya terhadap mortalitas nimfa dan keperidian wereng batang coklat (Nilaparvata lugens Stål) - Hendra, Yolma; Trizelia, Trizelia; Syahrawati, My (Perhimpunan Entomologi Indonesia, 2023)
Brown planthopper (BPH), Nilaparvata lugens Stål, is a significant pest widely recognised for its detrimental impact on rice production. Biological agents, such as the entomopathogenic fungus Beauveria bassiana (Bals.) Vuill., can effectively control this pest. B. bassiana, known for its endophytic abilities, colonises various plant tissues. This research aims to assess B. bassiana's colonosation capacity on rice plants and its impact on nymph mortality and BPH fecundity. Four isolates of B. bassiana (BbWS, Pb211, Td312, and BbJg) were used, each with conidial density of 108 conidia/ml. The application menthod involved soaking rice seeds in the fungus for 24 hours. The results showed that all B. bassiana isolates could successfully establish as endophytes within rice plants, colonising all tissue parts, with leaves exhibiting the highest fungal colonisation at 58%. Seed soaking with B. bassiana reduced eggs hatching by 23.88% and increased nymph mortality by 40%. The presence of B. bassiana in rice tissue also influenced BPH adults fecundity. Notably, the BbWS isolate demonstrated the most significant effectiveness in elevating nymph mortality and reducing BPH fecundity.